Cover Picture: Phys. Status Solidi C 6/2013. Issue 6 (4th June 2013) - Palashov, Oleg V.; Khazanov, Efim A.; Kravchenko, Valery B.; Fedorov, Pavel P.
<x xml:space="preserve">Abstract</x> In their paper on pp. 962–966, Hong Jin Kong, Sangwoo Park, Seongwoo Cha, and Jom Sool Kim propose a laser system that can produce 0.4 J/10 ns/10 kHz–4 kW, using a coherent beam combination with stimulated Brillouin scattering phase conjugate mirrors (SBS‐PCMs). With this 4 kW laser module, high‐power 2D holographic laser processing can be utilized. The coherent beam combination with SBS‐PCMs can be scaled to combine indefinitely many beams, making ultra high energy/high repetition rate pulsed lasers possible. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>